2021
DOI: 10.1038/s41598-021-94366-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bushen-Tiaojing-Fang on the pregnancy outcomes of infertile patients with repeated controlled ovarian stimulation

Abstract: Bushen-Tiaojing-Fang (BSTJF) is commonly used to treat infertility. This study investigated the effects of BSTJF on the pregnancy outcomes of patients with repeated controlled ovarian stimulation (COS), on mitochondrial function, and on oxidative stress in ovarian granulosa cells (GCs) and follicular fluid (FF). The samples and clinical data of 97 patients, including 35 in the control group, 29 in the placebo group and 33 in the BSTJF group, were collected for this study. The mitochondrial ultrastructure, ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It is however unfortunate that IVF-ET is not as successful as expected. [ 2 ] Study has shown that IVF-ET patients experience recurrent implantation failures in about 15% of cases. [ 3 ] In clinical practice, symptoms of threatened abortion (TA) such as vaginal bleeding and abdominal pain are very common during pregnancy of IVF-ET women.…”
Section: Introductionmentioning
confidence: 99%
“…It is however unfortunate that IVF-ET is not as successful as expected. [ 2 ] Study has shown that IVF-ET patients experience recurrent implantation failures in about 15% of cases. [ 3 ] In clinical practice, symptoms of threatened abortion (TA) such as vaginal bleeding and abdominal pain are very common during pregnancy of IVF-ET women.…”
Section: Introductionmentioning
confidence: 99%